Hydrothermal leaching behavior of complex polymetallic secondary sulfide concentrate enhanced by ultrasonic (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Complex polymetallic secondary sulfide concentrate is difficult to efficiently be utilized because of its special mineral phase structure and high content of lead and iron. A novelty process proposed in this study, hydrothermal leaching without acid enhanced by ultrasonic, could achieve eco-friendly and selective separation of copper and zinc from complex polymetallic secondary sulfide concentrate, inhibiting production of hazardous material plumboferrite contained in leaching residue. The influence of controlling parameters on the leaching efficiency and the mineral phase composition and structure of the obtained leaching residue were studied. The obtained results showed that, without sulfuric acid, the leaching efficiency of copper was the best under the conditions of temperature of 180 ℃, oxygen partial pressure of 1.0 MPa, stirring speed of 600 r/min, ultrasonic power of 360 W, liquid-solid ratio of 10:1 and mass ratio of lignosulfonate to raw material of 0.2%. Under the above optimal conditions, the leaching efficiency of zinc, copper and iron reached 99.88%, 99.12% and 19.46%, respectively. Ultrasonic enhancement increased the copper leaching efficiency by 10.02%, and promoted the leaching efficiency of iron decreased by 5.20%. The leaching process conformed to the unreacted contraction core model under mixed control, the activation energy was 71.76 kJ/mol, and the macroscopic kinetic equation related to stirring rate, oxygen partial pressure and ultrasonic power was 1-(1-X)1/3 -1/3ln(1-X) = 40.457 e(-8630.19/T)t。